Novel Antidepressants in the Pipeline (Phase II and III): A Systematic Review of the US Clinical Trials Registry - Sakurai, Hitoshi; Yonezawa, Kengo; Tani, Hideaki; Mimura, Masaru; Bauer, Michael; Uchida, Hiroyuki (Pharmacopsychiatry, 2022)
Introduction There is an imminent need for faster-acting and more effective antidepressants beyond the monoaminergic hypothesis.Methods We systematically searched the US Clinical Trials registry for antidepressant compounds with completed phase II and III trials. Compounds that demonstrated significant superiority over placebo in the primary outcome measure in the latest phase of phase II and III trials were identified. The collateral information was gathered via a PubMed search and press releases.Results Nine compounds were identified. AXS-05 (a combination of dextromethorphan and bupropion) and ansofaxine hydrochloride showed a positive result over placebo in a phase III study for major depressive disorder or treatment-resistant depression. MIJ821, nitrous oxide, psilocybin, ayahuasca, facial injection of botulinum toxin A, prasterone, and casopitant demonstrated at least one positive result in phase II trials. Ayahuasca showed a greater response rate than placebo at week one, indicating the rapid antidepressant effect.Discussion These new compounds with novel mechanisms of action are expected to provide a greater variety of treatment options for depression if preliminary positive results are confirmed.
Keywords: antidepressant; depression; fast-acting; pipeline; treatment-resistant depression